Bio-methane potential test (BMP) using inert gas sampling bags with macroalgae feedstock. (December 2015) - Edward, Membere; Edwards, Stephen; Egwu, Uchenna; Sallis, Paul
Abstract: An approach to Bio-methane potential test (BMP) was carried out at mesophilic temperature of 35 °C with Supel™ inert gas sampling bags as biogas collection and storage bags, using selected seaweed (macroalgae) as substrate. Samples were given a range of pre-treatments from washing, drying and macerating. Dried laminaria digitata (DD) with 68.14% VS (%TS) produced the highest BMP of 141 ± 5.77 L CH4 /kg VS, with methane content increasing to about 70%, while the lowest BMP of 93.35 ± 5.03 L CH4 /kg VS with methane content of about 65% was obtained for fresh laminaria digitata (FD) with 72.03% VS (%TS). Methane yields of 97.66 and 67.24 m 3 CH4 /t wet weight based on BMP results were obtained for DD and FD. Both DD and FD achieved within 28% and 38% of the theoretical BMP value based on the Buswell equation, respectively. The total methane (V) produced was computed based on; V  =  X 1  +  X 2  –  X 3 corrected to Standard temperature and pressure (STP). where X1  = daily calculated headspace methane volume, X2  = daily measured volume of methane in gas bags, X3  = previous day headspace methane volume. An advantage of this approach is the volumetric measurement of gas produced directly from the gas bags, hence it does not require liquid displacement or pressure transducers. Results from a second set of freshly collected sample seaweed sample showed it was in agreement with published BMP values. All analysis were carried out without mineral supplementation.